2020
DOI: 10.3389/fpsyg.2020.574847
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Cognition and Sensorimotor Behavior in an F1 Driving Simulation: An Explorative Study

Abstract: Sensorimotor control simultaneously engages multiple cognitive processes, like decision making, intention, processing, and the integration of multisensory signals. The reciprocal relationship of cognition and sensorimotor learning is well documented. However, little is known if the status of cognitive skills relates to immediate sensorimotor performance of performing a novel skill. Thus, we aim to explore whether cognitive skills in general and executive functions (EFs) in particular may relate to novel sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Altogether, results from studies 1 and 2 yielded evidence to support both the use and validity of our 4-instrument protocol to assess core and higher-level executive functioning among soccer and futsal athletes. However, we did not accomplish in totality, retrieving some results that only partially corroborated with previous literature, not entirely [ 14 18 , 21 – 26 , 56 , 57 ]. Nonetheless, to have a protocol that researchers from different areas of the globe can adopt and conduct their studies might ease the issues highlighted by Kalén et al [ 30 ], the excessive heterogeneity of measures leading to varied results that, as it happened in our studies, do not fully corroborate to each other.…”
Section: Discussionmentioning
confidence: 40%
See 3 more Smart Citations
“…Altogether, results from studies 1 and 2 yielded evidence to support both the use and validity of our 4-instrument protocol to assess core and higher-level executive functioning among soccer and futsal athletes. However, we did not accomplish in totality, retrieving some results that only partially corroborated with previous literature, not entirely [ 14 18 , 21 – 26 , 56 , 57 ]. Nonetheless, to have a protocol that researchers from different areas of the globe can adopt and conduct their studies might ease the issues highlighted by Kalén et al [ 30 ], the excessive heterogeneity of measures leading to varied results that, as it happened in our studies, do not fully corroborate to each other.…”
Section: Discussionmentioning
confidence: 40%
“…The study of Vestberg et al [ 16 ] found statistical difference in higher EFs among male soccer players from the first and the fourth division of the Swedish league, whereas our study did not find the same results regarding higher-order EF, we did find it in vWM and inhibition. Results comparing EFs in diverse levels of competitiveness were similar [ 14 , 17 , 18 , 21 – 26 ]. Which means that our study was able to reproduce previous findings in a sample of Brazilian female soccer and futsal players.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Very recently, Ludyga et al observed that the judo training program elicited benefits for response inhibition in preadolescent children 36 . Moreover, researchers have proposed that there is a meaningful relationship between response inhibition in the Stroop Colour and Word Test and driving performance 37 . Thus, the effectiveness of JEX training in this cognitive domain can directly translate into the everyday functioning of the elderly.…”
Section: Discussionmentioning
confidence: 99%